Polymer, method for preparing the same, positive electrode sheet, secondary battery, electric device
Patent Information
- Application Number
- CN202311098921.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2023-08-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-08-29
AI Technical Summary
[0005]二次电池中的极片往往是通过将含有活性材料的浆料涂覆在集流体上干燥后制备而成的,增加浆料中的溶剂含量、降低浆料的固含量是优化浆料分散均匀性、提高浆料涂覆质量的有效手段,然而高溶剂含量的浆料需要的干燥时间长、制造成本高,如何在提高浆料固含量的同时保证浆料的分散均匀性,进而有效地提高浆料最大固含量是本领域亟需解决的技术问题
[0077] Forming a carbon coating layer on the core surface can improve the conductivity of the positive electrode active material. When the sp(s) content in the carbon coating layer on the core surface increases... 2 When the molar ratio of hybrid carbon atoms to sp3 hybrid carbon atoms is not less than 0.5, the carbon coating structure of the positive electrode active material has a high degree of order, and the pore structure of the carbon coating has a high degree of density and a small pore size distribution range. During the battery production process, it is difficult for external moisture to enter the pores of the carbon coating, thereby effectively reducing the water absorption and water storage performance of the positive electrode active material, improving the battery safety and cycle performance, effectively saving energy consumption in the drying process, and significantly reducing production costs.
Smart Images

Figure CN119431767B_ABST
Abstract
Description
[0001] Cross-referencing
[0002] This application incorporates Chinese Patent Application No. 202310961340.X, filed on August 1, 2023, entitled “Polymer, Method of Preparation Thereof, Positive Electrode, Secondary Battery, Electrical Device”, which is incorporated herein by reference in its entirety. Technical Field
[0003] This application relates to the field of secondary battery technology, and in particular to a polymer, its preparation method, a positive electrode, a secondary battery, and an electrical device. Background Technology
[0004] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.
[0005] Electrodes in secondary batteries are often prepared by coating a slurry containing active materials onto a current collector and then drying it. Increasing the solvent content and reducing the solid content of the slurry are effective means to optimize the dispersion uniformity of the slurry and improve the coating quality. However, slurries with high solvent content require long drying times and have high manufacturing costs. How to ensure the dispersion uniformity of the slurry while increasing its solid content, and thus effectively increase the maximum solid content of the slurry, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] This application is made in view of the above-mentioned problems, and its purpose is to provide a dispersant that can increase the maximum solid content of slurry.
[0007] A first aspect of this application provides a polymer comprising the structure shown in Formula I.
[0008]
[0009] Wherein X includes a phosphate ester group or a phosphite ester group, R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment or a polyester segment; R2 contains an organic segment.
[0010] This polymer can effectively increase the maximum solid content of the cathode slurry, shorten the filtration time, and improve the production efficiency and quality of the electrode while improving the flexibility of the electrode.
[0011] In any embodiment, the organic segment of R2 contains at least one of amide group, amino group, and aryl group.
[0012] Nitrogen-containing or aryl groups in polymers help improve the anchoring effect between polymers and positive electrode active materials, making polymers particularly suitable for carbon-coated positive electrode active materials. This further enhances the versatility of polymers as dispersants. By increasing the anchoring sites of dispersants, the dispersing effect of polymers can be more effectively utilized, thereby further increasing the maximum solid content of the slurry, improving the quality of electrode forming while reducing costs and increasing efficiency.
[0013] In any embodiment, the organic segment of R2 also includes C. 2-12 Hydrocarbon group.
[0014] The polymer contains C 2-12 Hydrocarbon groups help to further improve the anchoring effect between polymers and carbon-modified cathode active materials. Hydrocarbon groups can effectively anchor carbon on cathode active materials, increasing the dispersibility of polymer anchoring sites on cathode active materials, thereby further improving the applicability of polymer dispersants, increasing the maximum solid content of slurry, optimizing electrode forming quality while reducing costs and increasing efficiency.
[0015] In any implementation, R2 includes the structure shown in Formula II.
[0016]
[0017] Among them, R4 and R5 are random copolymers, and R4 includes C 2-12 Hydroxyl group, C 3-13 At least one of the amide groups, R5 includes
[0018] At least one of them;
[0019] Where q1, q2, q3, and q4 each independently include any integer between 0 and 4, and R6 a R6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
[0020] The organic segments of the above structure can more effectively exert an anchoring effect through the copolymerization of nitrogen-containing groups and hydrocarbon groups, thereby enhancing the dispersion of the polymer and effectively increasing the solid content of the slurry.
[0021] In any implementation, R2 includes the structure shown in Formula III.
[0022]
[0023] Among them, R6 includes C 2-12 R7 includes alkylene groups. At least one of the following; wherein q5 and q6 each independently include any integer between 0 and 4, and 1 ≤ n ≤ 6.
[0024] The organic segments of the above structure can more effectively exert an anchoring effect through the alternating copolymerization of nitrogen-containing groups and hydrocarbon groups, thereby enhancing the dispersion of the polymer and effectively increasing the solid content of the slurry.
[0025] In any embodiment, the end group of R2 includes at least one of -C(O)-NH2 and -CH2-NH2.
[0026] Polymers with end groups including -C(O)-NH2 and -CH2-NH2 can more effectively exert a dispersing effect, increase the maximum solid content of the slurry, and thus improve the forming quality and efficiency of the electrode.
[0027] In any embodiment, at least one of R1 and R3 includes a polyether segment; optionally, both R1 and R3 include a polyether segment.
[0028] In any embodiment, at least one of R1 and R3 includes the polyether segment represented by formula IV.
[0029]
[0030] Where EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50.
[0031] The polyether segments with the above structure have suitable steric hindrance and low glass transition temperature, which can more effectively reduce the order of binder crystallization and glass transition temperature in the cathode slurry, thereby reducing the crystallinity of the binder, improving the flexibility of the electrode, and improving the uniformity and flexibility of the electrode through dispersion and softening effects. This improves the safety performance and ultimate compaction density of the battery, allowing for an increase in the loading of positive electrode active materials and further enhancing the energy density of the battery.
[0032] In any embodiment, the end groups of the polyether segments include aryl groups.
[0033] Aryl groups exhibit excellent compatibility with the carbon layer on the surface of the positive electrode active material, which helps to further improve the anchoring effect between the polymer and the carbon-modified positive electrode active material. By leveraging the effective anchoring of aryl groups with the carbon on the positive electrode active material, the dispersibility of the polymer anchoring sites on the positive electrode active material is increased, thereby further improving the applicability of the polymer dispersant, increasing the maximum solid content of the slurry, optimizing the electrode forming quality, and reducing costs and increasing efficiency.
[0034] In any embodiment, X comprises a phosphate group.
[0035] Phosphate ester polymers can more effectively increase the solid content of slurry, shorten filtration time, and improve electrode flexibility; moreover, phosphate ester polymers have better stability, and can effectively improve the cycle capacity retention rate of batteries while improving slurry dispersibility.
[0036] In any embodiment, the polymer comprises at least one of the polymers shown in the following formula:
[0037]
[0038]
[0039] Among them, at least one of R1 and R3 contains the block copolymer polyether segment shown in Formula IV.
[0040]
[0041] Where EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤15, 4≤n1≤15, and R6 and R4 each independently include C 4-8 Alkylene, C 4-8 At least one of the subalkenyl groups.
[0042] In any embodiment, the polymer is as follows:
[0043]
[0044] R2 includes at least one of hydrogen, aryl, substituted or unsubstituted alkyl, or an organic segment containing an amino or amide group.
[0045] At least one of R1 and R3 contains the block copolymer polyether segment shown in Formula IV.
[0046]
[0047] Wherein EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50, and the end groups of the polyether segments include phenyl groups. In any embodiment, the weight-average molecular weight of the polymer is 1000-10000, optionally 2000-5000.
[0048] Polymers with a weight-average molecular weight within the aforementioned range exhibit excellent dispersibility, further increasing the solids content of the slurry; they also provide excellent flow properties, reducing coating time and improving coating uniformity and speed. Polymers with a weight-average molecular weight of 2000-5000 can more effectively disperse, increasing the maximum solids content of the slurry and shortening filtration time.
[0049] A second aspect of this application provides a method for preparing a polymer, the method comprising:
[0050] A polymer containing the structure shown in Formula I is prepared by reacting the compound shown in Formula VI with R3OH, R1OH, water, and a polymeric monomer containing unsaturated bonds.
[0051]
[0052] Wherein, X includes a phosphate ester group or a phosphite ester group, and X1, X2, and X3 all contain halogens; R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment or a polyester segment; R2 includes an organic segment.
[0053] In any embodiment, the preparation method includes the following steps:
[0054] The intermediate product shown in Formula VII is prepared by reacting the compound shown in Formula VI with R3OH, R1OH, and water in a first reaction.
[0055]
[0056] The polymer is prepared by reacting the intermediate with a polymeric monomer containing at least one of an amide or an amine containing an unsaturated bond in a second reaction.
[0057] In any embodiment, the second reaction specifically includes the following steps:
[0058] The intermediate product undergoes an addition reaction with at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, followed by a substitution reaction with a halogen-substituted organic alcohol.
[0059] The polymer was prepared by repeating the above addition and substitution reactions in sequence multiple times.
[0060] R2 includes the structure shown in Equation III.
[0061]
[0062] Among them, R6 includes C 2-12 Hydrocarbon groups, R7 includes At least one of the following; wherein q5 and q6 each independently include any integer between 0 and 4, and 1 ≤ n ≤ 6.
[0063] In any embodiment, the preparation method further includes the following steps:
[0064] The intermediate product is reacted with at least one of (i) an amide containing an unsaturated bond, an amine containing an unsaturated bond, or (ii) a hydrocarbon monomer containing an unsaturated bond, or a cyclic amide monomer in a third reaction to prepare the polymer, wherein R2 comprises the structure shown in Formula II.
[0065]
[0066] Among them, R4 and R5 are random copolymers, and R4 includes C 2-12 hydrocarbon group, C 3-13 At least one of the amide groups, R5 includes
[0067] At least one of them;
[0068] Where q1, q2, q3, and q4 each independently include any integer between 0 and 4, and R6 a R6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
[0069] Another aspect of this application provides a method for preparing a polymer, the method comprising: reacting a compound of formula VI with a raw material containing R3OH and R1OH to prepare a polymer containing the structure of formula I.
[0070]
[0071] Wherein, X comprises a phosphate ester group or a phosphite ester group, and X1, X2, and X3 all contain halogens; R1 and R3 each independently comprise at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 comprises a polyether segment, wherein the end group of at least one of the polyether segments comprises an aryl group; R2 comprises an organic segment. A third aspect of this application provides the use of a polymer or a polymer prepared by any of the preparation methods thereof as a dispersant.
[0072] A fourth aspect of this application provides a positive electrode slurry comprising a dispersant, said dispersant comprising the polymer of claim 1 or the polymer prepared by the preparation method of claim 2.
[0073] This cathode slurry has a high solids content, which helps to improve the forming efficiency and quality of the cathode film, thereby enhancing the electrochemical performance and processing efficiency of the battery.
[0074] In any embodiment, the positive electrode slurry includes a positive electrode active material, which includes at least one lithium phosphate and its carbon-modified material; optionally, the positive electrode active material includes at least one lithium iron phosphate and its doped material, lithium manganese iron phosphate and its doped material, lithium iron phosphate and its doped material with carbon coating, and lithium manganese iron phosphate and its doped material with carbon coating.
[0075] The polymer is negatively charged, and its electrostatic interaction with the weakly acidic lithium phosphate further strengthens the mutual anchoring, thereby improving the polymer's dispersion effect on the lithium phosphate. Furthermore, lithium phosphate has poor conductivity; therefore, in the preparation of positive electrode active materials, sintering organic materials such as glucose or sucrose to coat the carbon layer is often used to improve its conductivity. This polymer also possesses groups that anchor to the carbon coating layer, exhibiting excellent dispersion of carbon-modified lithium phosphate, further improving the dispersibility of the slurry and thus increasing the maximum solids content of the slurry.
[0076] In any embodiment, the positive electrode active material includes a core and a carbon coating layer, wherein the carbon coating layer at least covers a portion of the surface of the core, and wherein the carbon coating layer contains sp 2 Hybridized carbon atoms and sp 3 The molar ratio of hybrid carbon atoms is not less than 0.2, and can be selected as not less than 0.5 or not less than 0.8.
[0077] Forming a carbon coating layer on the core surface can improve the conductivity of the positive electrode active material. When the sp(s) content in the carbon coating layer on the core surface increases... 2 When the molar ratio of hybrid carbon atoms to sp3 hybrid carbon atoms is not less than 0.5, the carbon coating structure of the positive electrode active material has a high degree of order, and the pore structure of the carbon coating has a high degree of density and a small pore size distribution range. During the battery production process, it is difficult for external moisture to enter the pores of the carbon coating, thereby effectively reducing the water absorption and water storage performance of the positive electrode active material, improving the battery safety and cycle performance, effectively saving energy consumption in the drying process, and significantly reducing production costs.
[0078] But sp 2 Hybridized carbon atoms and sp 3 Carbon coatings with a high degree of graphitization, where the molar ratio of hybrid carbon atoms is not less than 0.5, tend to agglomerate, making them difficult to disperse effectively during slurry preparation. The dispersant provided in this application, along with the highly graphitized carbon coating, possesses abundant anchoring groups, making it particularly suitable for dispersing highly graphitized cathode active materials. The combination of these two components can simultaneously improve both the battery's performance and processing capabilities.
[0079] In any embodiment, the thickness of the carbon coating layer is no greater than 15 nm; optionally, the thickness of the carbon coating layer is no greater than 10 nm, and optionally, the thickness of the carbon coating layer is 4 nm-8 nm. A carbon coating layer within the above thickness range can effectively improve the conductivity of the positive electrode active material by forming a thinner carbon coating layer on the surface of the core, and can also improve the compaction performance when using the positive electrode active material to prepare battery electrodes.
[0080] In any embodiment, based on the total dry mass of the positive electrode slurry, the mass content of the polymer is 0.1%-2.0%, optionally 0.2%-1.0%.
[0081] Polymers within the aforementioned range can effectively disperse the battery while maintaining its volumetric energy density, without significantly negatively impacting the battery's electrochemical performance.
[0082] In any embodiment, the positive electrode slurry includes a binder, the binder comprising a vinylidene fluoride polymer with a weight-average molecular weight of not less than 300,000, or optionally, the weight-average molecular weight of the binder being 700,000 to 9,000,000.
[0083] Polyvinylidene fluoride polymers with a weight-average molecular weight in this range have excellent bonding properties and electrochemical stability. Using polyvinylidene fluoride polymers with a weight-average molecular weight of 700,000 to 9,000,000 can further reduce the amount of polyvinylidene fluoride used, reduce the rigidity of the positive electrode film, improve the flexibility of the electrode, and thus improve the ultimate compaction density of the battery, helping to improve the energy density of the battery.
[0084] In any embodiment, the maximum solid content of the positive electrode slurry is not less than 60%, and can be selected as 60%-80%.
[0085] The fifth aspect of this application provides a positive electrode sheet, the positive electrode sheet including a positive electrode film layer, the positive electrode film layer being prepared by a positive electrode slurry according to any embodiment or the positive electrode film layer including a dispersant, the dispersant including the polymer of the first aspect or the polymer prepared by the preparation method of the second aspect.
[0086] In any embodiment, the positive electrode sheet has a compaction density of 2.6 g / cm³. 3 The number of folds required is no less than 2, and can be 3-6.
[0087] Polymers can not only effectively increase the solid content of slurry, but also act as a flexible agent to improve the flexibility of the positive electrode sheet, thereby further improving the safety and electrochemical performance of the battery.
[0088] In any embodiment, the areal density of the positive electrode sheet is not less than 300 mg / 1540.25 cm³. 2The option is 300mg / 1540.25cm. 2 -600 mg / 1540.25cm 2 .
[0089] Polymers can effectively increase the maximum solid content of slurry, increasing the coating speed by more than 30%. They are especially suitable for high-speed coating and thick coating molding methods, effectively solving the problem of easy cracking of electrode sheets during thick coating, and helping to prepare positive electrode sheets with high flexibility and no cracks after winding.
[0090] In any embodiment, the positive electrode film layer includes a dispersant comprising the structure shown in Formula I.
[0091]
[0092] Wherein X includes a phosphate ester group or a phosphite ester group, R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment or a polyester segment, and R2 contains an organic segment; optionally, the organic segment of R2 contains at least one of an amide group and an amino group, and optionally, the end group of the polyether segment includes an aryl group; the positive electrode active material includes at least one of lithium iron phosphate and its doped materials, lithium manganese iron phosphate and its doped materials, lithium iron phosphate and its doped carbon-coated materials, and lithium manganese iron phosphate and its doped carbon-coated materials; optionally, the positive electrode active material includes at least one of lithium manganese iron phosphate and its doped materials, and lithium manganese iron phosphate and its doped carbon-coated materials; based on the total mass of the positive electrode film, the mass content of the dispersant is 0.1%-2.0%, optionally 0.2%-1.0%.
[0093] This positive electrode film has good dispersibility and processability, which is beneficial to improving manufacturing efficiency and battery performance.
[0094] The sixth aspect of this application provides a secondary battery, including the positive electrode sheet of the fifth aspect.
[0095] The seventh aspect of this application provides an electrical device including the secondary battery of the sixth aspect. Attached Figure Description
[0096] Figure 1 This is a schematic diagram of the polymer dispersion mechanism according to an embodiment of this application;
[0097] Figure 2 This is a schematic diagram of a secondary battery according to one embodiment of this application;
[0098] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of this application is shown.
[0099] Figure 4 This is a schematic diagram of a battery module according to one embodiment of this application;
[0100] Figure 5 This is a schematic diagram of a battery pack according to one embodiment of this application;
[0101] Figure 6 yes Figure 5 An exploded view of a battery pack according to one embodiment of this application is shown;
[0102] Figure 7 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.
[0103] Explanation of reference numerals in the attached figures:
[0104] 1 Battery pack; 2 Upper casing; 3 Lower casing; 4 Battery module; 5 Secondary battery; 51 Housing; 52 Electrode assembly; 53 Cover plate; 6 Polymer; 61 Anchoring group; 62 Flexible segment; 7 Positive electrode active material. Detailed Implementation
[0105] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the polymer, its preparation method, positive electrode, secondary battery, and electrical device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0106] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0107] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0108] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0109] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0110] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0111] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0112] To improve the kinetic and electrochemical performance of batteries, the synthesis of positive electrode active materials tends towards nano-scale and denser carbon coating. This results in a larger specific surface area for the positive electrode active materials, requiring more solvent for effective dispersion during the slurry mixing process, thus reducing the solid content of the slurry. Low-solid-content slurries necessitate longer drying times during electrode coating and drying, leading to lower production efficiency and higher energy consumption. Furthermore, prolonged heating and drying of low-solid-content slurries may cause problems such as electrode edge curling, cracking, and binder floating, deteriorating electrode quality.
[0113] Based on this, the first aspect of this application provides a polymer comprising the structure shown in Formula I.
[0114]
[0115] Wherein X includes a phosphate ester group or a phosphite ester group, R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment or a polyester segment; R2 contains an organic segment.
[0116] In this article, polymers include, on the one hand, chemically homogeneous aggregates of macromolecules prepared by polymerization reactions, but differing in degree of polymerization, molar mass, and chain length; on the other hand, they also include derivatives of such macromolecular aggregates formed by polymerization reactions, i.e., polymers that can be obtained by reactions of the functional groups in the aforementioned macromolecules, such as addition or substitution, and can be chemically homogeneous or chemically heterogeneous.
[0117] In some embodiments, the polymer includes phosphate ester polymers. The structure of phosphate ester polymers is shown in Formula V:
[0118]
[0119] In some embodiments, the polymer includes phosphite polymers. The structural formula of a phosphite polymer is shown in V':
[0120]
[0121] In this paper, polyether segments refer to polymer segments whose structural units contain ether bonds (-COC-).
[0122] In this paper, polyester segments refer to polymer segments whose structural units contain ester groups (-COO-).
[0123] In this article, hydrocarbon groups refer to groups containing carbon and hydrogen atoms, including but not limited to alkyl, alkenyl, and alkynyl groups.
[0124] In this paper, organic segments can be formed by the polymerization of repeating structural units or by organic groups formed from small molecule monomers. The dispersion mechanism of the polymers provided in the embodiments of this application is as follows: Figure 1 As shown, polymer 6 includes anchoring groups 61 and flexible segments 62. The anchoring group 61 at one end of polymer 6 acts on the surface of the positive electrode active material 7, achieving dispersion through the steric hindrance effect of the flexible segments 62. The phosphate or phosphite groups in polymer 6 can be effectively anchored to the surface of the positive electrode active material 7 through intermolecular forces or electrostatic interactions, thus functioning as anchoring groups 61. Through the anchoring effect of the anchoring groups on the surface of the positive electrode active material, the steric hindrance effect of flexible segments 62, such as polyether and polyester segments, is effectively exerted on the surface of the positive electrode active material particles, preventing the agglomeration of the positive electrode active material 7. This increases the amount of positive electrode active material 7 that can be effectively dispersed within a unit volume of solvent, reduces gelation and agglomeration of the slurry during homogenization, reduces slurry viscosity, significantly increases the effective solid content of the slurry, reduces slurry filtration time, and improves the forming efficiency and quality of the electrode sheet. The polymer provided in this application embodiment enables the slurry to be suitable for thick coating processes, contributing to the improvement of battery energy density.
[0125] Meanwhile, the flexible segments such as polyether segments and polyester segments in the polymer have suitable steric hindrance and low glass transition temperature, which can improve the flexibility of the electrode through the movement of the flexible segments, and simultaneously play the roles of dispersion and flexibility enhancement.
[0126] In some embodiments, the organic segment of R2 contains at least one of amide, amino, and aryl groups.
[0127] In this article, amide group refers to The group includes primary amides, secondary amides, and tertiary amides.
[0128] In this article, amino group refers to The group includes primary amino groups, as well as secondary and tertiary amino groups.
[0129] In this document, "aryl" refers to an organic group derived from a monocyclic or polycyclic aromatic hydrocarbon by removing a hydrogen atom. As examples, aryl groups include, but are not limited to, phenyl, naphthyl, and benzyl. Aryl groups may be unsubstituted or substituted with one or more suitable substituents.
[0130] Furthermore, the aryl group can be monocyclic or polycyclic. In some embodiments, the aryl group contains at least 6, 7, 8, 9, or 10 carbon atoms. Characterization of polymers containing amide groups using infrared absorption spectroscopy revealed that the carbonyl group is located at 1900 cm⁻¹. -1 ~1650cm -1 The absorption peak in the band, and the amide group located at 3500 cm⁻¹ -1 ~3100cm -1 A medium-intensity bimodal absorption peak in the band.
[0131] Nitrogen-containing or aryl groups in polymers help improve the anchoring effect between polymers and positive electrode active materials, making polymers particularly suitable for carbon-coated positive electrode active materials. This further enhances the versatility of polymers as dispersants. By increasing the anchoring sites of dispersants, the dispersing effect of polymers can be more effectively utilized, thereby further increasing the maximum solid content of the slurry, improving the quality of electrode forming while reducing costs and increasing efficiency.
[0132] In some embodiments, the organic segment of R2 also contains C 2-12 Hydrocarbon group.
[0133] In this article, "C 2-12 A "hydrocarbon group" refers to a straight-chain or branched hydrocarbon group composed only of carbon and hydrogen atoms. The group may or may not contain unsaturated carbon atoms, has two to twelve carbon atoms, and is attached to the rest of the molecule by at least one single bond. C 2-12 Examples of hydrocarbon groups include, but are not limited to: C 2-12 Alkyl, C 2-12 Alkylene, C 2-12 alkenyl, C 2-12 Alkenyl groups. Examples include ethylene, ethyl, n-propyl, 1-methylethyl (isopropyl), isopropylene, 1,3-propylene, butyl, isobutyl, tert-butyl, 1,4-butylene, 1,3-butylene, 2-butenylene, pentyl, isopentyl, neopentyl, hexyl, heptyl, octyl, etc. Polymers containing C 2-12 Hydrocarbon groups help to further improve the anchoring effect between polymers and carbon-modified cathode active materials. Hydrocarbon groups can effectively anchor carbon on cathode active materials, increasing the dispersibility of polymer anchoring sites on cathode active materials, thereby further improving the applicability of polymer dispersants, increasing the maximum solid content of slurry, optimizing electrode forming quality while reducing costs and increasing efficiency.
[0134] In some implementations, R2 comprises the structure shown in Formula II:
[0135]
[0136] Among them, R4 and R5 are random copolymers, and R4 includes C2-12 Hydroxyl group, C 3-13 At least one of the amide groups, R5 includes
[0137] At least one of them;
[0138] Where q1, q2, q3, and q4 each independently include any integer between 0 and 4, and R6 a R6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
[0139] C 2-12 Hydroxyl groups refer to divalent hydrocarbon groups with 2-12 carbon atoms; including C 2-12 Alkylene, C 2-12 Alkenyl group. As an example, C 2-12 Alkylenes include, but are not limited to, 1,2-ethylene, 1,2-propylene, 1,3-propylene, 1,3-butylene, 1,4-butylene, 2-methyl-1,3-propylene, 1,1-dimethyl-1,2-ethylene, 1,4-pentanediene, 1,5-pentanediene, 2-methyl-1,4-butylene, 2,2-dimethyl-1,3-propylene, 1,6-hexanediene, and 2-methyl-1,5-pentanediene. 3-methyl-1,5-pentylene, 2,3-dimethyl-1,4-butylene, 1,7-heptene, 2-methyl-1,6-hexylene, 3-methyl-1,6-hexylene, 2-ethyl-1,5-pentylene, 3-ethyl-1,5-pentylene, 2,3-dimethyl-1,5-pentylene, 2,4-dimethyl-1,5-pentylene, 1,8-octylene, 2-methyl-1,7-heptene 3-methyl-1,7-heptene, 4-methyl-1,7-heptene, 2-ethyl-1,6-hexene, 3-ethyl-1,6-hexene, 2,3-dimethyl-1,6-hexene, 2,4-dimethyl-1,6-hexene, 1,9-nonene, 2-methyl-1,8-octene, 3-methyl-1,8-octene, 4-methyl-1,8-octene, 2-ethyl-1,7- Heptene, 3-ethyl-1,7-heptene, 1,10-decene, 2-methyl-1,9-nonene, 3-methyl-1,9-nonene, 4-methyl-1,9-nonene, 5-methyl-1,9-nonene, 1,11-undecene, 2-methyl-1,10-decene, 3-methyl-1,10-decene, 5-methyl-1,10-decene, 1,12-dodecene.
[0140] C 2-12 The alkenyl group is a divalent hydrocarbon group containing at least one double bond. As an example, C 2-12The term "alkenyl" includes, for example, vinylidene, propenyl, 1-methylvinylidene, 1-butenyl, 2-butenyl, 1-methylpropenyl, 2-methylpropenyl, 1-pentenyl, 2-pentenyl, 1-methyl-1-butenyl, 1-methyl-2-butenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 1-methyl-1-pentenyl, 1-methyl-2-pentenyl, 1-methyl-3-pentenyl, 1,4-dimethyl-1-butenyl, 1,4-dimethyl-2-butenyl, 1-heptenyl, 2-heptenyl, 3-heptenyl, 1-octenyl, 2-octenyl, and 3-octenyl.
[0141] In some implementations, C 3-13 The amide group contains the following groups:
[0142] Where x is 2 to 12, and can be 2 to 5.
[0143] In some implementations, x is 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12.
[0144] In this article, C 1-4 Alkyl groups include at least one of methyl, ethyl, propyl, isopropyl, 2-methyl-1-propyl, and 2-methyl-2-propyl.
[0145] In some implementations, s can be any one of 1, 2, 3, 4, 5, or 6.
[0146] In some implementations, t is any one of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10.
[0147] In some implementations, q1, q2, q3, and q4 are each independently selected from 0, 1, 2, 3, or 4.
[0148] The organic segments of the above structure include nitrogen-containing groups and hydrocarbon groups, which can more effectively exert anchoring effects, enhance polymer dispersion, and effectively increase the solid content of the slurry.
[0149] In some embodiments, R2 includes the structure shown in Formula III.
[0150]
[0151] Among them, R6 includes C 2-12 R7 includes alkylene groups. At least one of the following; wherein q5 and q6 each independently include any integer between 0 and 4, and 1 ≤ n ≤ 6.
[0152] In some implementations, q5 and q6 each independently include 0, 1, 2, 3 or 4.
[0153] In some implementations, n is any one of 1, 2, 3, 4, 5, and 6.
[0154] The organic segments of the above structure can more effectively exert anchoring effect through the alternating arrangement of nitrogen-containing groups and hydrocarbon groups, thereby enhancing the dispersion effect of the polymer and effectively increasing the solid content of the slurry.
[0155] In some embodiments, the end group of R2 includes at least one of -C(O)-NH2 and -CH2-NH2.
[0156] Polymers with end groups including -C(O)-NH2 and -CH2-NH2 can more effectively exert a dispersing effect, increase the maximum solid content of the slurry, and thus improve the forming quality and efficiency of the electrode.
[0157] In some embodiments, at least one of R1 and R3 contains a polyether segment; alternatively, both R1 and R3 contain polyether segments. Characterization of the polymer containing the polyether segment using infrared absorption spectroscopy revealed that the ether bond absorption peak is located in the range of 1250–1100 cm⁻¹. -1 Band.
[0158] In some embodiments, R2 includes at least one of H and aryl.
[0159] In some embodiments, one of R1 and R3 comprises a polyether segment, and the other comprises C 1-4 alkyl.
[0160] In some embodiments, both R1 and R3 include polyether segments.
[0161] Both R1 and R3 contain polyether segments, while R1 and R3 contain C. 1-4 Alkyl groups and polymers further optimize the filtration properties of the slurry and improve the flexibility of the electrode.
[0162] In some embodiments, at least one of R1 and R3 comprises a polyether segment represented by formula IV.
[0163]
[0164] Where EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50.
[0165] In some embodiments, the polyether segments are block copolymer segments. In some embodiments, the polyether segments are random copolymer segments.
[0166] In some implementations, m1 and n1 can be independently selected from 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20, 25, 30, 35, 40, 45, 50 or any value between any two.
[0167] The polyether segments with the above structure have suitable steric hindrance and low glass transition temperature, which can more effectively reduce the order of binder crystallization and glass transition temperature in the cathode slurry, thereby reducing the crystallinity of the binder, improving the flexibility of the electrode, and improving the uniformity and flexibility of the electrode through dispersion and softening effects. This improves the safety performance and ultimate compaction density of the battery, allowing for an increase in the loading of positive electrode active materials and further enhancing the energy density of the battery.
[0168] In some embodiments, the end groups of the polyether segments include aryl groups.
[0169] The aryl group exhibits excellent compatibility with the carbon layer on the surface of the positive electrode active material, which helps to further improve the anchoring effect between the polymer and the carbon-modified positive electrode active material. The effective anchoring of the aryl group with the carbon on the positive electrode active material increases the dispersibility of the polymer anchoring sites on the positive electrode active material, thereby further expanding the applicability of the polymer dispersant, increasing the maximum solid content of the slurry, optimizing the electrode forming quality, and reducing costs while increasing efficiency. In some embodiments, X includes a phosphate ester group.
[0170] Phosphate ester polymers can more effectively increase the solid content of slurry, shorten filtration time, and improve electrode flexibility; moreover, phosphate ester polymers have better stability, and can effectively improve the cycle capacity retention rate of batteries while improving slurry dispersibility.
[0171] In some embodiments, the polymer includes at least one polymer represented by the following formula:
[0172]
[0173] Among them, at least one of R1 and R3 contains the block copolymer polyether segment shown in Formula IV.
[0174]
[0175] Where EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤15, 4≤n1≤15.
[0176] In some implementations, R6 and R4 each independently include C. 4-8 Alkylene, C 4-8 At least one of the subalkenyl groups.
[0177] In some embodiments, R6 and R4 each independently include -(CH2)4-, -(CH2)5-, -(CH2)6-, -(CH2)7-, -(CH2)8-, At least one of the groups.
[0178] In some embodiments, the end groups of the polyether segments include phenyl groups.
[0179] In some embodiments, the polymer is as follows:
[0180]
[0181] Wherein, R2 includes at least one of hydrogen, aryl, substituted or unsubstituted alkyl, and organic segments containing amino or amide groups, and at least one of R1 and R3 includes a block copolyether segment of Formula IV.
[0182]
[0183] Wherein EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50, and the end groups of the polyether segments include phenyl groups.
[0184] In some embodiments, the weight-average molecular weight of the polymer is 1,000-10,000, optionally 2,000-5,000.
[0185] Weight-average molecular weight has a meaning well-known in the art and can be measured by methods well-known in the art. As an example, weight-average molecular weight can be measured by gel permeation chromatography.
[0186] In some embodiments, the weight-average molecular weight of the polymer is 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000 or any value between them.
[0187] Polymers with a weight-average molecular weight within the aforementioned range exhibit excellent dispersibility, further increasing the solids content of the slurry; they also provide excellent flow properties, reducing coating time and improving coating uniformity and speed. Polymers with a weight-average molecular weight of 2000-5000 can more effectively disperse, increasing the maximum solids content of the slurry and shortening filtration time.
[0188] A second aspect of this application provides a method for preparing a polymer, the method comprising the following steps:
[0189] A polymer containing the structure shown in Formula I is prepared by reacting the compound shown in Formula VI with R3OH, R1OH, water, and a polymeric monomer containing unsaturated bonds.
[0190]
[0191] Wherein, X includes a phosphate ester group or a phosphite ester group, and X1, X2, and X3 all contain halogens; R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment or a polyester segment; R2 includes an organic segment.
[0192] In this document, halogens include at least one of fluorine, chlorine, bromine, and iodine.
[0193] In some embodiments, phosphorus and oxygen are linked by a double bond in Formula VI, and X is a phosphate ester group in Formula I.
[0194] In some embodiments, Formula VI does not include oxygen, and X in Formula I is a phosphite group.
[0195] In some implementations, formula VI includes POCl3 or PCl3.
[0196] In some embodiments, the preparation method includes the following steps:
[0197] The intermediate product shown in Formula VII is prepared by reacting the compound shown in Formula VI with R3OH, R1OH, and water in a first reaction.
[0198]
[0199] The polymer is prepared by reacting the intermediate with a polymeric monomer containing at least one of an amide or an amine containing an unsaturated bond in a second reaction.
[0200] In some implementations, the first reaction specifically includes:
[0201] R3OH was added dropwise to the compound shown in Formula VI under stirring. The reaction temperature was kept below 20°C. After stirring for a period of time, the temperature was raised to 40-50°C and reacted for 6-7 hours. Water was then added, and the reaction was carried out at 50-60°C for 3-4 hours to obtain the first intermediate product shown in Formula A. The molar ratio of R3OH to the compound shown in Formula VI was 1.2-1.5, wherein R3 includes C 1-4 alkyl,
[0202]
[0203] The above reaction conditions are beneficial to improving the purity of the product.
[0204] In some implementations, the first reaction also includes:
[0205] The polyether is reacted with the first intermediate at 100°C-120°C for 4-7 hours to produce the intermediate shown in Formula VII, wherein R1 contains a polyether segment.
[0206] In some embodiments, the second reaction specifically includes the following steps:
[0207] The intermediate product undergoes an addition reaction with at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, followed by a substitution reaction with a halogen-substituted organic alcohol.
[0208] The polymer was prepared by repeating the above addition and substitution reactions multiple times.
[0209] R2 includes the structure shown in Equation III.
[0210]
[0211] Among them, R6 includes C 2-12 Hydrocarbon groups, R7 includes At least one of the following; wherein q5 and q6 each independently include any integer between 0 and 4, and 1 ≤ n ≤ 6.
[0212] An addition reaction is a reaction in which the π bond in a double bond breaks, forming two single bonds.
[0213] Substitution reactions are a type of chemical reaction in which one atom or group replaces another atom or group in an organic molecule and occupies its position.
[0214] In some embodiments, the preparation method further includes the following steps:
[0215] The intermediate product is reacted with at least one of (i) an amide containing an unsaturated bond, an amine containing an unsaturated bond, or (ii) a hydrocarbon monomer containing an unsaturated bond, or a cyclic amide monomer in a third reaction to prepare the polymer, wherein R2 comprises the structure shown in Formula II.
[0216]
[0217] Among them, R4 and R5 are random copolymers, and R4 includes C 2-12 hydrocarbon group, C 3-13 At least one of the amide groups, R5 includes
[0218] At least one of them;
[0219] Where q1, q2, q3, and q4 each independently include any integer between 0 and 4, and R6 a R6 b Contains hydrogen, C 1-4At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
[0220] In some embodiments, the hydrocarbon monomer containing unsaturated bonds includes at least one of olefin monomers, alkyne monomers, and cyclic alkanes.
[0221] In some embodiments, cyclic amide monomers refer to cyclic monomers that include amide bonds.
[0222] In some embodiments, the third reaction specifically includes reacting the mixed intermediate with at least one of a hydrocarbon monomer containing an unsaturated bond and a cyclic amide monomer for a period of time, followed by adding at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond to undergo a copolymerization reaction.
[0223] In some embodiments, the preparation method further includes the following steps:
[0224] Polymers with hydroxyl-terminated groups are capped with unsaturated monomers containing amide or amino groups to prepare polymers with amide or amino-terminated groups.
[0225] This application provides a method for preparing a polymer, the method comprising:
[0226] The compound of formula VI is reacted with a starting material containing R3OH and R1OH to prepare a polymer containing the structure of formula I.
[0227]
[0228] Wherein, X includes a phosphate ester group or a phosphite ester group, and X1, X2, and X3 all contain halogens; R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment, wherein the end group of at least one of the polyether segments includes an aryl group; R2 includes an organic segment.
[0229] In some embodiments, the monomer shown in Formula VI is reacted with R1OH and R3OH in an inert or alkaline environment, and then water or phenol is added to react and obtain a polymer.
[0230] In some embodiments, the polymer containing hydroxyl groups in R2 is further reacted with a polymeric monomer containing at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond to prepare a polymer containing nitrogen in R2.
[0231] In some embodiments, the polymers of any embodiment of this application and the polymers prepared by the preparation methods of any embodiment of this application are used as dispersants.
[0232] In some embodiments, the polymers of any embodiment of this application and the polymers prepared by the preparation methods of any embodiment of this application are used as dispersants in secondary battery electrode slurries.
[0233] In some embodiments, the polymers of any embodiment of this application and the polymers prepared by the preparation methods of any embodiment of this application are used as dispersants in the positive electrode slurry of secondary batteries.
[0234] [Positive electrode slurry]
[0235] A third aspect of this application provides a positive electrode slurry, which includes a dispersant comprising a polymer as described in any embodiment or a polymer prepared by any method described in any embodiment.
[0236] This cathode slurry has a high solids content, which helps to improve the forming efficiency and quality of the cathode film, thereby enhancing the electrochemical performance and processing efficiency of the battery.
[0237] In some embodiments, the positive electrode slurry includes a positive electrode active material, said positive electrode active material including at least one lithium phosphate and its carbon-modified material.
[0238] In some embodiments, the lithium-containing phosphate includes at least one of lithium iron phosphate and its doped materials, and lithium manganese iron phosphate and its doped materials. In some embodiments, the doped material includes a doped material at any site, optionally lithium-site doped, phosphorus-site doped, manganese-site doped, or iron-site doped.
[0239] In some embodiments, the carbon-modified material includes at least one of carbon-coated materials and carbon-doped materials.
[0240] In some embodiments, the positive electrode active material includes at least one of lithium iron phosphate and its doped materials, lithium manganese iron phosphate and its doped materials, lithium iron phosphate and its doped materials with carbon coating, and lithium manganese iron phosphate and its doped materials with carbon coating.
[0241] The polymer is negatively charged, and its electrostatic interaction with the weakly acidic lithium phosphate further strengthens the mutual anchoring, thereby improving the polymer's dispersion effect on the lithium phosphate. Furthermore, lithium phosphate has poor conductivity; therefore, in the preparation of positive electrode active materials, sintering organic materials such as glucose or sucrose to coat the carbon layer is often used to improve its conductivity. This polymer also possesses groups that anchor to the carbon coating layer, exhibiting excellent dispersion of carbon-modified lithium phosphate, further improving the dispersibility of the slurry and thus increasing the maximum solids content of the slurry.
[0242] In some embodiments, the positive electrode active material includes a core and a carbon coating layer, the carbon coating layer at least covering a portion of the surface of the core, wherein the carbon coating layer contains sp2 Hybridized carbon atoms and sp 3 The molar ratio of hybrid carbon atoms is not less than 0.2, and can be selected as not less than 0.5 or not less than 0.8.
[0243] In some embodiments, sp2 hybridized carbon atoms in the carbon coating layer are combined with sp... 3 The molar ratio of hybrid carbon atoms can be selected as 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or any value range between the two.
[0244] The carbon structure and characteristics of the carbon coating can be determined using methods known in the art. As an example, this can be done using Raman spectroscopy. Specifically: first, the Raman spectrum of the cathode material is measured; then, by peak separation of the Raman spectrum, Ig / Id (where Id is the sp...) is obtained. 3 Peak intensity of hybrid carbon atoms, Ig is sp 2 The peak intensity of the hybrid carbon atom, the ratio of this peak intensity to sp. 2 The peak height of hybrid carbon atoms and sp 3 The ratio of the peak heights of hybridized carbon atoms (to obtain sp) 2 Hybridized carbon and sp 3 The molar ratio of hybrid carbon. The sp(s) content in the carbon coating layer of the positive electrode active material. 2 Hybridized carbon atoms and sp 3 The molar ratio of hybridized carbon atoms is not particularly restricted; for example, sp in the carbon coating layer. 2 Hybridized carbon atoms and sp 3 The molar ratio of hybrid carbon atoms can be not less than 0.5. In some embodiments, the sp atoms in the carbon coating layer... 2 Hybridized carbon atoms and sp 3 The molar ratio of hybridized carbon atoms can be no less than 0.8. When the sp atoms in the carbon coating layer... 2 Hybridized carbon atoms and sp 3 When the molar ratio of hybrid carbon atoms is within the above range, the carbon coating layer on the core surface has a high degree of graphitization and a more compact structure. This reduces the water absorption of the carbon coating layer and enables it to achieve good conductivity, ensuring the lithium ion pathway and improving the cycle performance and safety performance of the positive electrode active material.
[0245] In some embodiments, the core comprises a phosphate; in some embodiments, the phosphate comprises at least one of lithium manganese phosphate, lithium iron phosphate, lithium manganese iron phosphate, and doped materials thereof.
[0246] Forming a carbon coating layer on the core surface can improve the conductivity of the positive electrode active material. When the sp(s) content in the carbon coating layer on the core surface increases... 2When the molar ratio of hybrid carbon atoms to sp3 hybrid carbon atoms is not less than 0.5, the carbon coating structure of the positive electrode active material has a high degree of order, and the pore structure of the carbon coating has a high degree of density and a small pore size distribution range. During the battery production process, it is difficult for external moisture to enter the pores of the carbon coating, thereby effectively reducing the water absorption and water storage performance of the positive electrode active material, improving the battery safety and cycle performance, effectively saving energy consumption in the drying process, and significantly reducing production costs.
[0247] But sp 2 Hybridized carbon atoms and sp 3 Carbon coatings with a high degree of graphitization, where the molar ratio of hybrid carbon atoms is not less than 0.5, tend to agglomerate, making them difficult to disperse effectively during slurry preparation. The dispersant provided in this application, along with the highly graphitized carbon coating, possesses abundant anchoring groups, making it particularly suitable for dispersing highly graphitized cathode active materials. The combination of these two components can simultaneously improve both the battery's performance and processing capabilities.
[0248] In some implementations, the kernel includes Li 1+x Mn 1-y A y P 1-z R z O4, where x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and R includes one or more elements selected from B (boron), S, Si, and N. The manganese doping element A selected from the above elements helps to reduce the lattice change rate of lithium manganese phosphate during lithium insertion / extraction, improves the structural stability of the positive electrode active material, significantly reduces manganese dissolution, and lowers the oxygen activity on the particle surface. The phosphorus doping element R selected from the above elements also helps to change the ease of Mn-O bond length changes, thereby improving electronic conductivity and lowering the lithium-ion migration barrier, promoting lithium-ion migration, and improving the rate performance of the secondary battery.
[0249] Unless otherwise stated, in the above-described core chemical formula, when a doping site has two or more elements, the limitations on the numerical ranges of x, y, z, or m are not only limitations on the stoichiometry of each element serving as that site, but also limitations on the sum of the stoichiometry of all elements serving as that site. For example, when the core has the chemical formula Li... 1+x Mn 1- y AyP 1-z R zWhen A is a compound of O4, and A consists of two or more elements A1, A2...An, the stoichiometric coefficients y1, y2...yn of each of A1, A2...An must each fall within the numerical range of y defined in this application, and the sum of y1, y2...yn must also fall within this numerical range. Similarly, for the case where R consists of two or more elements, the limitation on the numerical range of the stoichiometric coefficient of R in this application has the same meaning.
[0250] According to some embodiments of this application, the type of kernel is not particularly limited; for example, the kernel may include Li 1+ x C m Mn 1-y A y P 1-z R z O 4-n D nThe value of x is influenced by the valence states of A and R, as well as the values of y and z, to ensure the overall system remains electrically neutral. If the value of x is too small, the lithium content of the entire core system will decrease, affecting the specific capacity of the material. More specifically, x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, n is any value in the range of 0.001 to 0.1, and m is any value in the range of 0.9 to 1.1. For example, 1+x is selected from the range of 0.9 to 1.1, such as 0.97, 0.977, 0.984, 0.988, 0.99, 0.991, 0.992, 0.993, 0.994, 0.995, 0.996, 0.997, 0.998, 1.01; x is selected from the range of 0.001 to 0.1, such as 0.001, 0.005; and y is selected from the range of 0.001 to 0.5, such as 0.001. The values are 0.005, 0.02, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.34, 0.345, 0.349, 0.35, and 0.4, where z is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, 0.08, and 0.1, and n is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, 0.08, and 0.1, and the positive electrode active material is electrically neutral. C includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo, and W; A includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge; R includes one or more elements selected from B (boron), S, Si, and N; and D includes one or more elements selected from S, F, Cl, and Br. By simultaneously doping specific elements at specific amounts at the Li, Mn, P, and O sites of the compound, significantly improved rate performance can be obtained, while significantly reducing the dissolution of Mn and Mn-site dopants, resulting in significantly improved cycle performance and / or high-temperature stability. Furthermore, the specific capacity and tap density of the positive electrode active material can also be improved.
[0251] In some embodiments, the thickness of the carbon coating layer is no greater than 15 nm; optionally, the thickness of the carbon coating layer is no greater than 10 nm, or optionally, the thickness of the carbon coating layer is 4 nm-8 nm.
[0252] In some embodiments, the thickness of the carbon coating can be selected as 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm or any value range between the two.
[0253] The thickness of the carbon coating layer can be measured as follows: A thin slice approximately 100 nm thick is cut from the middle of a single positive electrode active material particle using a fiber-optic blot (FIB). The slice is then subjected to transmission electron microscopy (TEM) to obtain the original TEM image, which is saved in xx.dm3 format. The original TEM image is opened in Digital Micrograph software. The carbon coating layer is identified using lattice spacing and angle information, and its thickness is measured. The thickness is measured at three locations on the selected particle, and the average value is taken.
[0254] The carbon coating layer within the aforementioned thickness range can effectively improve the conductivity of the positive electrode active material by forming a thinner carbon coating layer on the surface of the core, and can also improve the compaction performance when using the positive electrode active material to prepare battery electrodes.
[0255] In some embodiments, the positive electrode active material is prepared by the following method:
[0256] A core is provided; a carbon coating layer is formed on at least a portion of the surface of the core, wherein the molar ratio of sp2 hybridized carbon atoms to sp3 hybridized carbon atoms in the carbon coating layer is not less than 0.2, and optionally not less than 0.5.
[0257] In some embodiments, forming a carbon coating layer on at least a portion of the surface of the core includes: forming a pre-carbon coating layer on the surface of the core using a carbon source to obtain a pre-coated positive electrode active material; and sintering the pre-coated positive electrode active material to form the carbon coating layer to obtain the positive electrode active material, wherein the carbon source includes a first carbon source and a second carbon source.
[0258] In some embodiments, a pre-carbon coating layer is formed on the core surface to obtain a pre-coated positive electrode active material. The method for forming the pre-carbon coating layer on the core surface is not particularly limited. For example, the carbon source and the core can be placed in the same reaction vessel, and hydrothermal treatment can be used to cause the carbon source to react on the core surface, thereby forming a carbon coating layer. Alternatively, the carbon source and the core can be placed in a ball mill, such as a sand mill, and mechanical mixing can be used to form a carbon coating layer on the core surface. In some embodiments, the carbon source includes a first carbon source and a second carbon source. The first carbon source includes at least one selected from polyvinyl alcohol, polyethylene glycol, and citric acid; the second carbon source includes at least one selected from starch, sucrose, and glucose. In some embodiments, the molecular weight of the first carbon source is not less than 1000; in other embodiments, the molecular weight of the first carbon source can be 2000-5000. Thus, ball milling can form a uniformly distributed pre-carbon coating layer with a relatively consistent thickness on the core surface, which is beneficial for forming a dense and uniform carbon coating layer pore structure after sintering. In some embodiments, the second carbon source may include at least one selected from starch, sucrose, and glucose. In some embodiments, the second carbon source may be glucose.
[0259] In some embodiments, the pre-coated positive electrode active material is sintered under an inert gas atmosphere. In some embodiments, the pre-coated positive electrode active material is sintered to obtain the positive electrode active material. The sintering process should be carried out under an inert atmosphere to avoid oxidation of the carbon source, which would prevent the formation of a carbon coating layer with a high degree of graphitization. The type of inert gas is not particularly limited; for example, the inert gas may include at least one of nitrogen and helium. The sintering conditions are not particularly limited; for example, the sintering temperature may be 650°C-800°C, and the sintering time may be 6h-12h. This allows a carbon coating layer with a high degree of graphitization to be formed on the core surface. As the sintering temperature increases, the degree of graphitization of the carbon in the carbon coating layer also increases. By controlling the maximum sintering temperature, the degree of graphitization of the carbon coating layer can be effectively controlled, resulting in a carbon coating layer with a dense porous structure and superior conductivity.
[0260] In some embodiments, forming a carbon coating layer on at least a portion of the surface of the core includes: mixing the core with a first carbon source and obtaining a first coated positive electrode active material through a first sintering process; mixing the first coated positive electrode active material with a second carbon source and obtaining the positive electrode active material through a second sintering process.
[0261] In some embodiments, the temperature of the first sintering treatment is 350℃-800℃, and the time of the first sintering treatment is 6h-12h. In some embodiments, the temperature of the second sintering treatment is 650℃-850℃, and the time of the second sintering treatment is 6h-24h.
[0262] In some embodiments, the polymer content is 0.1%-2.0% by mass, optionally 0.2%-1.0%, based on the total dry mass of the positive electrode slurry.
[0263] In some embodiments, based on the total dry mass of the positive electrode slurry, the mass content of the polymer can be selected as 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or any value between these ranges. Polymers within the above ranges can effectively disperse the material while maintaining the volumetric energy density of the battery, without significantly negatively impacting the battery's electrochemical performance.
[0264] In some embodiments, the positive electrode slurry includes a binder comprising a vinylidene fluoride polymer with a weight-average molecular weight of not less than 300,000, or optionally, the weight-average molecular weight of the binder is 700,000 to 9,000,000.
[0265] In some embodiments, the vinylidene fluoride polymer is a vinylidene fluoride homopolymer.
[0266] In some embodiments, the vinylidene fluoride polymer is a vinylidene fluoride copolymer.
[0267] Weight-average molecular weight has a well-known meaning in the art and can be tested by any known method. In some embodiments, the weight-average molecular weight of the binder is characterized by gel permeation chromatography.
[0268] In some embodiments, the weight-average molecular weight of the adhesive can be selected as 700,000, 1,000,000, 2,000,000, 3,000,000, 4,000,000, 5,000,000, 6,000,000, 7,000,000, 8,000,000, 9,000,000 or any value therebetween.
[0269] Polyvinylidene fluoride polymers with a weight-average molecular weight in this range have excellent bonding properties and electrochemical stability. Using polyvinylidene fluoride polymers with a weight-average molecular weight of 700,000 to 9,000,000 can further reduce the amount of polyvinylidene fluoride used, reduce the rigidity of the positive electrode film, improve the flexibility of the electrode, and thus improve the ultimate compaction density of the battery, helping to improve the energy density of the battery.
[0270] In some embodiments, the maximum solid content of the positive electrode slurry is not less than 60%, and can be selected as 60%-80%.
[0271] The maximum solids content of the cathode slurry refers to the maximum solids content of the slurry that meets the requirements of a shipping viscosity between 4000 and 35000 mPa·s, and that does not exhibit gelation after standing for 24 hours. The actual solids content test method for the cathode slurry is as follows: Record the slurry weight as m0 and place it in a weight loss rate testing instrument; evaporate the solvent until the weight loss rate is below 0.3%, and record the remaining weight as m1; solids content = m1 / m0 * 100%.
[0272] In some embodiments, the maximum solid content of the positive electrode slurry can be selected as 60%, 65%, 70%, 75%, 80%, or any value between them.
[0273] By adding polymers to the positive electrode slurry, the solid content and flexibility of the slurry are effectively increased, thereby improving the flexibility and molding efficiency of the electrode sheet.
[0274] [Positive electrode plate]
[0275] This application also provides a positive electrode sheet, which includes a positive electrode film layer. The positive electrode film layer is prepared by a positive electrode slurry according to any embodiment, or the positive electrode film layer includes a dispersant, which includes a polymer according to any embodiment or a polymer prepared by any embodiment of the preparation method.
[0276] In some implementations, the positive electrode film layer is disposed on one or both of the two opposing surfaces of the positive electrode current collector.
[0277] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0278] In some embodiments, the positive electrode sheet has a compaction density of 2.6 g / cm³. 3 The number of folds required is no less than 2, and can be 3-6.
[0279] The positive electrode sheet has a compaction density of 2.6 g / cm³. 3 The number of times an electrode can be folded in half can be used to characterize its flexibility and can be measured by any known method. As an example, a defect-free electrode with a compacted density of 2.6 g / cm³ is used. 3The positive electrode sheet was cut longitudinally into samples measuring 25cm x 4cm, with at least four samples. Each sample was pre-folded in half along the longitudinal direction (25cm direction), then placed on a testing platform and rolled once with a 2kg cylindrical roller. If light was transmitted, the test was considered brittle and passed through once. If no light was transmitted, the reverse folding and rolling process was repeated. The creases were observed against the light to check for light transmission or breakage. The actual number of folds was recorded. Four tests were performed, and the average was taken as the test result.
[0280] In some embodiments, the positive electrode sheet has a compaction density of 2.6 g / cm³. 3 The number of times the fold can be made is 2, 3, 4, 5 or 6.
[0281] Polymers can not only effectively increase the solid content of slurry, but also act as a flexible agent to improve the flexibility of the positive electrode sheet, thereby further improving the safety and electrochemical performance of the battery.
[0282] In some embodiments, the areal density of the positive electrode is not less than 300 mg / 1540.25 cm³. 2 The option is 300mg / 1540.25cm. 2 -600 mg / 1540.25cm 2 .
[0283] In some embodiments, the areal density of the positive electrode is 300 mg / 1540.25 cm³. 2 400mg / 1540.25cm 2 450mg / 1540.25cm 2 500mg / 1540.25cm 2 600mg / 1540.25cm 2 Or any value in between. The areal density of the electrode has a known meaning and can be measured by any known method.
[0284] In some embodiments, the positive electrode comprises lithium iron phosphate, and the areal density of the positive electrode is not less than 360 mg / 1540.25 cm³. 2 The option is 360mg / 1540.25cm. 2 -600mg / 1540.25cm 2 .
[0285] In some embodiments, the positive electrode comprises lithium iron manganese phosphate, and the areal density of the positive electrode is not less than 300 mg / 1540.25 cm³. 2 The option is 300mg / 1540.25cm. 2 -600mg / 1540.25cm 2 .
[0286] Polymers can effectively increase the maximum solid content of slurry, increasing the coating speed by more than 30%. They are especially suitable for high-speed coating and thick coating molding methods, effectively solving the problem of easy cracking of electrode sheets during thick coating, and helping to prepare positive electrode sheets with high flexibility and no cracks after winding.
[0287] In some embodiments, the positive electrode film layer includes a dispersant comprising the structure shown in Formula I.
[0288]
[0289] Wherein X includes a phosphate ester group or a phosphite ester group, R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment or a polyester segment, and R2 contains an organic segment; optionally, the organic segment of R2 contains at least one of an amide group and an amino group; optionally, the end group of the polyether segment includes an aryl group; the positive electrode active material includes at least one of lithium iron phosphate and its doped materials, lithium manganese iron phosphate and its doped materials, lithium iron phosphate and its doped carbon-coated materials, and lithium manganese iron phosphate and its doped carbon-coated materials; optionally, the positive electrode active material includes at least one of lithium manganese iron phosphate and its doped materials, and based on the total mass of the positive electrode film, the mass content of the dispersant is 0.1%-2.0%, optionally 0.2%-1.0%.
[0290] This positive electrode film exhibits good dispersibility and processability, which is beneficial for simultaneously improving manufacturing efficiency and battery performance. In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0291] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder, and dispersant, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing, and other processes.
[0292] [Negative electrode plate]
[0293] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0294] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0295] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0296] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0297] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0298] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0299] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0300] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0301] [Electrolytes]
[0302] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0303] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0304] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0305] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0306] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0307] [Isolation membrane]
[0308] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0309] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0310] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0311] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0312] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0313] [Rechargeable Battery]
[0314] Another aspect of this application provides a secondary battery, which includes a positive electrode sheet according to any embodiment.
[0315] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 This is an example of a square-structured secondary battery 5. The secondary battery can also be a sodium-ion battery, a magnesium-ion battery, or a potassium-ion battery.
[0316] In some implementations, refer to Figure 3 The outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 can be placed over the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly 52 using a winding or stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The secondary battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.
[0317] [Battery Module]
[0318] In some implementations, the secondary batteries can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.
[0319] Figure 4 This is battery module 4, used as an example. (See reference...) Figure 4 In battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.
[0320] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.
[0321] [Battery Pack]
[0322] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0323] Figure 5 and Figure 6 This is battery pack 1 as an example. (See reference...) Figure 5 and Figure 6 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0324] [Electrical appliances]
[0325] In one embodiment of this application, an electrical device is provided, including at least one of a secondary battery, a battery module, or a battery pack according to any embodiment.
[0326] The electrical device includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0327] As the electrical device, a secondary battery, battery module, or battery pack can be selected according to its usage requirements.
[0328] Figure 7This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0329] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a rechargeable battery as their power source.
[0330] Example
[0331] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0332] Example 1
[0333] 1) Preparation of dispersants:
[0334] Preparation of the first intermediate product
[0335] POCl3 was added to a four-necked flask equipped with a thermometer, stirrer, and hydrogen chloride gas collection device. R3OH was then added dropwise while stirring, maintaining the reaction temperature below 20°C. After stirring for 20 min, the temperature was raised to 40-50°C, where n(POCl3):n(R3-OH) was 1.2-1.5. After reacting for 6-7 h, a certain amount of distilled water was added dropwise, and the reaction was continued at 55°C for 3.5 h to prepare the first intermediate product. The yield of the first intermediate product can be ≥95% by controlling the reaction parameters, where R3 is -CH2CH3.
[0336]
[0337] Preparation of the second intermediate:
[0338] Weigh 0.4% of the total mass of 1,2-propylene glycol (ethylene oxide, propylene oxide monomer, and the first intermediate product) and 0.3% of the total mass of concentrated sulfuric acid into the reactor. Close the reactor lid and tighten the fixing bolts with a wrench. Evacuate the reactor and purge it three times with high-purity nitrogen. Add ethylene oxide and propylene oxide sequentially at a molar ratio of n2:m2 to initiate a block polymerization reaction. Maintain the pressure at 0.3±0.05 MPa and the temperature at 115±5℃. After 5 hours of reaction, add the first intermediate product. React at 115±5℃ for another 5 hours to generate the second intermediate product. The reaction process is illustrated in the diagram below, where A1 represents... n2 is 25, m2 is 25, and R3 is -CH2CH3.
[0339]
[0340] Preparation of polymers:
[0341] The second intermediate was reacted with acrylamide at room temperature for 12 hours, followed by the addition of HO(CH2)4Cl and a substitution reaction at room temperature under alkaline conditions for 6 hours. This addition and substitution reaction were then repeated once to prepare the product shown in formula X, with R6 as -(CH2)4- and n as 2, as shown in the figure below. The polymer's weight-average molecular weight is 3109.
[0342]
[0343] 2) Preparation of positive electrode slurry:
[0344] Lithium iron phosphate (LFP@C) with carbon coating as the positive electrode active material, carbon black (SP) as the conductive agent, polyvinylidene fluoride (PVDF) as the binder, and dispersant (the above polymers) were added to N-methylpyrrolidone (NMP) in a mass ratio of 96.5:2:1:0.5. The mass fraction of the dispersant was 0.5% of the dry material in the slurry, and the weight average molecular weight of PVDF was 700,000. The carbon coating layer of lithium iron phosphate contains SP... 2 Hybridized carbon atoms and sp 3 The molar ratio of hybrid carbon atoms is 0.271.
[0345] 3) Preparation of the positive electrode sheet:
[0346] The positive electrode slurry was uniformly coated onto both surfaces of the aluminum foil positive electrode current collector, and then dried to obtain a film layer. After cold pressing and slitting, the positive electrode sheet was obtained, with an areal density of 450 mg / 1540.25 mm². 2 .
[0347] 4) Preparation of negative electrode sheet
[0348] The negative electrode active material artificial graphite, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water in a weight ratio of 96:2:1:1 and mixed evenly to prepare a negative electrode slurry. The negative electrode slurry is then coated evenly on both surfaces of the negative electrode current collector copper foil multiple times. After drying, cold pressing, and slitting, the negative electrode sheet is obtained.
[0349] 5) Separating membrane
[0350] Polypropylene film is used as the separator.
[0351] 6) Preparation of electrolyte
[0352] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), the organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed evenly at a volume ratio of 3 / 7. The lithium salt LiPF6 is then dissolved in the organic solvent to prepare a solution with a mass content of 12.5%, thus obtaining the electrolyte.
[0353] 7) Preparation of secondary batteries
[0354] The positive electrode, separator, and negative electrode prepared in Example 1 are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. They are then wound to obtain a bare cell. Tabs are welded to the bare cell, which is then placed in an aluminum casing and baked at 80°C to remove moisture. Electrolyte is then injected and the casing is sealed to obtain a non-charged battery. The non-charged battery then undergoes a series of processes including settling, hot and cold pressing, formation, shaping, and capacity testing to obtain the lithium-ion battery product of Example 1.
[0355] Example 2
[0356] The preparation method is similar to that of Example 1, except that the type of dispersant is changed. The first two steps of the dispersant synthesis process are the same as those of Example 1. The nitrogen-containing monomer added in the third step is 3-amino-1-propene. The dispersant structure is as follows, where R1, R3, R6, and n are the same as those of Example 1.
[0357]
[0358] Example 3
[0359] The preparation method is similar to that of Example 1, except that the type of dispersant is changed. The first two steps of the dispersant synthesis process are the same as in Example 1. The third step, the preparation process of the polymer, is as follows:
[0360] Butadiene was added to the second intermediate and reacted at 100°C for 0.5 h, followed by the addition of acrylamide. The reaction was then carried out at 110°C under alkaline conditions for 6 h to obtain the polymer. The reaction diagram is shown below, where R1 and R3 are consistent with those in Example 1, s is 3, t is 3, and the structural units derived from butadiene and acrylamide are random copolymers.
[0361]
[0362] Example 4
[0363] The preparation method is similar to that of Example 1, except that the type of dispersant is changed. The first two steps of the dispersant synthesis process are the same as in Example 1. The third step, the preparation process of the polymer, is as follows:
[0364] Butadiene was added to the second intermediate and reacted at 100°C for 0.5 h. Then 3-amino-1-propene was added and reacted at 110°C in an alkaline environment for 6 h to obtain the polymer. The reaction diagram is shown in the figure below. R1 and R3 are consistent with those in Example 1, s is 3, t is 3, and the structural units derived from butadiene and 3-amino-1-propene are random copolymers.
[0365]
[0366] Example 5
[0367] The preparation method is similar to that of Example 1, except that the type of dispersant is changed. The first two steps of the dispersant synthesis process are the same as in Example 1. The preparation process of the polymer is as follows:
[0368] Butadiene was added to the second intermediate and reacted at 100°C for 6.5 h under alkaline conditions to obtain the polymer. The reaction diagram is shown below, where R1 and R3 are consistent with those in Example 1, and s+t is 6.
[0369]
[0370] Example 6
[0371] The preparation method is similar to that of Example 1, except that the dispersant is different. The dispersant is prepared by further reacting the product of Example 1 with 3-amino-1-propene to prepare a polymer with amino-terminated groups, as shown below, where R1, R3, R6, and n are consistent with those in Example 1.
[0372]
[0373] Example 7
[0374] The preparation method is similar to that of Example 1, except that the product of Example 1 is further reacted with acrylamide to prepare a polymer with amide end groups, as shown below, wherein R1, R3, R6, and n are consistent with those in Example 1.
[0375]
[0376] The preparation methods of Examples 8-15 are similar to those of Example 7. The difference is that in Examples 8-11, the weight-average molecular weight of the polymer is controlled by adjusting the degree of polymerization of the polyether segments, and in Examples 12-15, the amount of dispersant added is adjusted to keep the total mass of the positive electrode film unchanged. With the change of the mass content of the dispersant, the mass percentage of the positive electrode active material is adjusted accordingly. See Table 1 for specific parameters.
[0377] The preparation method of Example 16 is similar to that of Example 3, except that the organic monomer containing unsaturated bonds added during the polymer preparation process in the dispersant preparation process is... The structural formula of the dispersant prepared with m=4 is as follows:
[0378] R1, R3, s, and t are consistent with those in Example 3.
[0379] Example 17
[0380] Example 17 is prepared in a similar manner to Example 7, except that the monomers used in the preparation of R1 are ethylene oxide, and therefore the polyether segment is polyethylene oxide.
[0381] Example 18
[0382] The preparation methods of Example 18 and Example 7 are basically the same, except that the anchoring group of the dispersant in Example 7 is a phosphite group. The preparation method is basically the same as the preparation method of the dispersant in Example 7. The difference is that the initial input in the preparation process is not POCl3, but PCl3. The structure of the dispersant is shown below, wherein R1, R3, R6, and n are consistent with those in Example 1.
[0383]
[0384] Example 19
[0385] The preparation methods of Example 19 and Example 7 are basically the same. The difference is that in Example 19, the R3 group and the R1 group are the same, both of which are polyether segments, and n2 is 12 and m2 is 13 in both cases.
[0386] The preparation process of the dispersant is basically the same as in Example 7, except that the preparation process of the second intermediate product is different, as detailed below:
[0387] Weigh 0.4% of the total mass of 1,2-propylene glycol (ethylene oxide, propylene oxide monomer, and POCl3) and 0.3% of the total mass of concentrated sulfuric acid into the reactor. Close the reactor lid and tighten the fixing bolts with a wrench. Evacuate the reactor and purge it three times with high-purity nitrogen. Add ethylene oxide and propylene oxide sequentially at a molar ratio of n2:m2 to initiate a block polymerization reaction. Maintain the pressure at 0.3±0.05 MPa and the temperature at 115±5℃. After 5 hours of reaction, add POCl3, dichloromethane (DCM), and sodium hydroxide. React for another 5 hours under a nitrogen atmosphere at 115±5℃. Then add water and react at 50℃ for 10 hours to generate the product. The reaction process is illustrated in the diagram below, where A1 represents... n² is 12, m² is 13.
[0388]
[0389] The product was reacted in the same manner as in Example 7 to bind the R2 group, generating a phosphorus-containing polymer, which was used as a dispersant.
[0390] Example 20
[0391] The preparation methods of Example 20 and Example 7 are basically the same, except that the weight average molecular weight of the binder PVDF is 300,000; the ratio of the positive electrode active material carbon-coated lithium iron phosphate (LFP@C), conductive agent carbon black (SP), binder polyvinylidene fluoride (PVDF), and dispersant is 96:2:1.5:0.5.
[0392] Example 21
[0393] Example 21 uses the material prepared in Example 19 It is used directly as a dispersant and no longer binds to the R2 group.
[0394] Example 22
[0395] Example 22 is prepared in a manner similar to that of Example 19, except that the initial input during the synthesis of the polyether segment in the dispersant preparation process is phenol instead of 1,2-propanediol, and the catalyst is potassium hydroxide, wherein A1 is... n2 is 12, m2 is 13, R6 is -(CH2)4-, and n is 2.
[0396] Specifically, the dispersant is:
[0397]
[0398] Example 23
[0399] In Example 23, the product prepared during the synthesis process of Example 22 was used directly as a dispersant, and its specific structural formula is as follows:
[0400]
[0401] Example 24
[0402] The preparation methods of Example 24 and Example 23 are basically the same, except that in the final step of the product preparation process, water is not added for hydrolysis. Instead, phenol is added and reacted at 50°C for 10 hours to generate the product, which is then used directly as a dispersant. The specific structural formula is as follows:
[0403]
[0404] Example 25
[0405] The preparation methods of Example 25 and Example 7 are basically the same, except that the initial input in the polyether segment synthesis process is not 1,2-propanediol, but phenol, and A1 in the product is phenyl.
[0406] Example 26
[0407] The preparation methods of Example 26 and Example 22 are basically the same, except that the positive electrode active material is carbon-coated lithium manganese iron phosphate, and its preparation method is as follows:
[0408] Step S1: Add 689.6g of manganese carbonate, 455.27g of ferrous carbonate, 4.65g of cobalt sulfate, and 4.87g of vanadium dichloride to a mixer and mix thoroughly for 6 hours. Then transfer the resulting mixture to a reaction vessel, add 5L of deionized water and 1260.6g of oxalic acid dihydrate, heat to 80℃, and stir thoroughly at 500rpm for 6 hours until the mixture is homogeneous and the reaction terminates without the generation of bubbles, obtaining a Fe, Co, and V co-doped manganese oxalate suspension. Then filter the suspension, dry it at 120℃, and then mill it to obtain Fe, Co, V, and S co-doped manganese oxalate particles with a particle size of 100nm.
[0409] Step S2: Take 1793.1g of manganese oxalate, 368.3g of lithium carbonate, 1146.6g of ammonium dihydrogen phosphate, and 4.9g of dilute sulfuric acid prepared in Step S1, add them to 20L of deionized water, stir thoroughly, and react uniformly at 80℃ for 10h to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation to obtain a powder. In a protective atmosphere (90% nitrogen and 10% hydrogen), sinter the powder in a roller kiln at 700℃ for 4h to obtain the core of the positive electrode active material: Li0.997Mn0.60Fe0.393V0.004Co0.003P0.997S0.003O4.
[0410] Step S3: Using PEG-3000 as the first carbon source, 58.2g of PEG-1000 was dissolved in 500g of deionized water, then stirred and fully dissolved to obtain an aqueous solution. 1571.9g of the above core material was added to the solution and stirred for 6 hours until homogeneous. After spray drying, a first sintering treatment was performed at a temperature of 600℃ for 9 hours, thereby obtaining the first coated positive electrode active material.
[0411] Step S4: Using glucose as the second carbon source, 37.3g of glucose was dissolved in 500g of deionized water, then stirred and fully dissolved to obtain a glucose aqueous solution. 1603.3g of the first coated positive electrode active material obtained in Step S3 was added to the aforementioned glucose solution and stirred together for 6 hours until homogeneous. After spray drying, a second sintering treatment was performed at 750℃ for 20 hours, thus obtaining the positive electrode active material.
[0412] Examples 27-28
[0413] The preparation methods of Examples 27 and 28 are basically the same as those of Example 26, except that the preparation method of the positive electrode active material is different. The specific difference parameters are as follows:
[0414] In Example 27, the first carbon source was PEG-10000, the first sintering temperature was 500℃, and the first sintering time was 5h. The second carbon source was glucose, the second sintering temperature was 550℃, and the second sintering time was 20h.
[0415] In Example 28, the first carbon source was PEG-2000, the first sintering temperature was 660℃, and the first sintering time was 9h. The second carbon source was sucrose, the second sintering temperature was 750℃, and the second sintering time was 6h.
[0416] Comparative Example
[0417] Comparative Example 1
[0418] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that no dispersant is added.
[0419] The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that the dispersant used is...
[0420]
[0421] Where a is 3 and b is 3.
[0422] Comparative Example 3
[0423] The preparation methods of Comparative Example 3 and Example 26 are basically the same, except that the dispersant in Comparative Example 3 is the same as that in Comparative Example 2.
[0424] Comparative Example 4
[0425] The preparation methods of Comparative Example 4 and Example 27 are basically the same, except that the dispersant in Comparative Example 4 is the same as that in Comparative Example 2.
[0426] Comparative Example 5
[0427] The preparation methods of Comparative Example 5 and Example 28 are basically the same, except that the dispersant in Comparative Example 5 is the same as that in Comparative Example 2.
[0428] II. Performance Testing
[0429] 1. Characterization of polymers
[0430] 1) Weight-average molecular weight
[0431] A Waters 2695 Isocratic HPLC gel electrophoresis system (differential refractive index detector 2141) was used. A 3.0% polystyrene solution was used as a reference, and a matched column was selected (oil-based: Styragel HT5 DMF7.8*300mm + Styragel HT4). A 3.0% polymer solution was prepared using purified N-methylpyrrolidone (NMP) solvent and allowed to stand for one day. For testing, tetrahydrofuran was first used to flush the syringe, repeated several times. Then, 5 ml of the experimental solution was drawn, air was expelled from the syringe, and the needle tip was dried. Finally, the sample solution was slowly injected into the injection port. Data was acquired after the reading stabilized.
[0432] 2. Positive electrode active material
[0433] 1) Determination of the hybridization mode of carbon atoms in the carbon coating layer:
[0434] Determination of the hybridization morphology of carbon atoms in the carbon coating layer: This test was performed using Raman spectroscopy. By peak separation of the Raman spectrum, I was obtained. g / I d , where I d For sp 3 Peak intensity of carbon speciation, I g For sp 2 The peak intensity of carbon in different forms is used to determine the molar ratio between the two.
[0435] 2) Carbon coating thickness test
[0436] The thickness of the carbon coating layer was measured by cutting a thin slice of approximately 100 nm thickness from the middle of a single particle of the aforementioned positive electrode active material using FIB (fiber optics). The slice was then subjected to TEM (thermometry) to obtain the raw TEM image, which was saved in the original image format (xx.dm3). The raw TEM image was opened in Digital Micrograph software, and the carbon coating layer was identified using lattice spacing and angle information. The thickness of the carbon coating layer was then measured. The thickness was measured at three locations on the selected particle, and the average value was taken.
[0437] 3. Positive electrode slurry
[0438] 1) Maximum solids content of slurry
[0439] The maximum solids content of the cathode slurry refers to the maximum solids content of the slurry that meets the requirements of a shipping viscosity between 4000 and 35000 mPa·s and that does not gel after standing for 24 hours. The solids content testing method is as follows: Record the weight of the slurry as m0 and place it in a weight loss rate testing instrument; evaporate the solvent until the weight loss rate is below 0.3%, and record the remaining weight as m1; solids content = m1 / m0 * 100%.
[0440] 2) Filtration time
[0441] Take an area of 30×30cm 2 Fold a 200-mesh filter into a funnel shape; take two beakers, place one on the table, and fill the other with 500ml of slurry. Pour the slurry into the filter funnel and record the filtration time when 300ml of slurry drips down.
[0442] 4. Positive electrode sheet
[0443] 1) Electrode brittleness test
[0444] Take a defect-free sample with a compacted density of 2.6 g / cm³. 3 The positive electrode sheet was cut longitudinally into samples measuring 25cm x 4cm, with at least four samples. Each sample was pre-folded in half longitudinally (25cm direction), then placed on a testing platform and rolled once with a 2kg cylindrical roller. If light was transmitted, the brittle light transmission test was performed once. If no light was transmitted, the reverse folding and rolling test was repeated. The creases were observed against the light to check for light transmission or breakage. The actual number of folds was recorded, and the average number was taken as the test result.
[0445] 5. Secondary batteries
[0446] 1) Maximum volumetric energy density
[0447] Maximum volumetric energy density refers to the volumetric energy density of the battery measured when the positive electrode is at its ultimate compaction density. The ultimate compaction density is defined as the smaller of the compaction density corresponding to an electrode elongation of 6‰ or an electrode flexibility fold of 2 times.
[0448] The method for measuring the discharge energy of a single battery cell is as follows:
[0449] The battery cells were left to stand at 25°C for 2 hours to ensure the temperature remained at 25°C. At 25°C, the battery cells were charged at 0.33C to the charging cutoff voltage, and then continued to be charged at this cutoff voltage under constant voltage until the current reached 0.05C, at which point charging was stopped (where C represents the rated capacity of the battery cell). After leaving the battery cells to stand at 25°C for 1 hour, they were discharged at 0.33C to the discharge cutoff voltage at 25°C. The total discharge capacity C0 and total discharge energy of the battery cells were recorded.
[0450] The method for measuring the volume of a single battery cell is as follows:
[0451] Measure the length, width, and height of each battery cell to calculate the battery cell volume value M0.
[0452] The formula for calculating battery energy density is as follows:
[0453] Battery energy density = Discharge energy of a single battery cell E0 / Volume of a single battery cell M0.
[0454] 2) Cyclic capacity retention rate at 25°C for 40 cycles
[0455] The voltage calibration method is as follows:
[0456] The battery cells were left to stand at 25°C for 2 hours to ensure the temperature remained at 25°C. At 25°C, the battery cells were charged to 4.25V at a rate of 0.33C0, then charged at a constant voltage of 4.25V until a current of 0.05C0 was reached, followed by a 1-hour rest. At 25°C, the cells were discharged to 0.95C0 at a rate of 0.33C0, and the voltage V1 was recorded. After resting for 5 minutes, the cells were discharged to 2.0V at 25°C at a rate of 0.33C0. After resting for 5 minutes, the battery cells were charged to 0.97C0 at 25°C at a rate of 0.33C0, and the voltage V2 was recorded.
[0457] The loop test process is as follows:
[0458] The battery cells were left to stand at 25°C for 2 hours to ensure the temperature remained at 25°C. The cells were then charged to voltage V2 at 0.33C0 at 25°C and left to stand for 0.5 hours. The cells were then discharged to voltage V1 at 0.33C0 at 25°C, and the capacity at this point was recorded as Cn. After standing for 0.5 hours, the above steps were repeated until the number of cycles n reached 40cls.
[0459] After cycling for 40cls following the above steps, record Cn / C0 as the cycle capacity retention rate, which serves as an indicator for evaluating battery cycle performance.
[0460] 3) Full battery cycle count test:
[0461] Under constant temperature conditions of 45℃, the full battery was charged at 1C to 4.3V within a range of 2.5V-4.3V. Then, it was charged at a constant voltage of 4.3V until the current was less than or equal to 0.05mA. After resting for 5 minutes, it was discharged at 1C to 2.5V, and the discharge capacity at this point was recorded as D0. This charge-discharge cycle was repeated until the discharge capacity decreased to 80% of D0. The number of cycles completed at this point was recorded.
[0462] III. Analysis of Test Results for Each Embodiment and Comparative Example
[0463] Table 1
[0464]
[0465] As can be seen from the comparison between the examples and the comparative examples, all examples include the polymer dispersant shown in Formula I, which can effectively increase the maximum solid content of the slurry, shorten the filtration time, and improve the production efficiency and quality of the electrode while improving the flexibility of the electrode.
[0466] As can be seen from the comparison between Examples 1-4 and Example 5, the presence of at least one of amide groups and amino groups in the organic segments of R2 can further increase the maximum solids content of the slurry.
[0467] As can be seen from the comparison between Examples 6-7 and Example 1, the end groups of R2 containing at least one of -C(O)-NH2 and -CH2-NH2 can more effectively exert the dispersing effect of the polymer and increase the maximum solid content of the slurry compared with other end groups.
[0468] As can be seen from the comparison between Example 7 and Example 17, at least one of R1 and R3 containing poly(ethylene oxide-propylene oxide) polyether segments can more effectively exert the dispersing and softening effect compared with polyethylene oxide polyether segments, further improving the maximum solid content of the slurry and the flexibility of the electrode.
[0469] As can be seen from the comparison between Example 19 and Example 7, since both R1 and R3 are polyether segments, compared to only one of the two being a polyether segment, the slurry filtration time can be further reduced and the electrode flexibility can be improved.
[0470] As can be seen from the comparison of Examples 7-11, a polymer with a weight-average molecular weight of 2000-5000 can further enhance the dispersing effect, increase the maximum solid content of the slurry, and shorten the filtration time.
[0471] Table 2
[0472]
[0473] As can be seen from the comparison between Example 22 and Example 19, Example 25 and Example 7, and Example 23 and Example 21, the end groups of the polyether segments include phenyl groups, which can further improve the dispersibility of the slurry.
[0474] Table 3
[0475]
[0476] As can be seen from Examples 12-15, based on the total dry mass of the cathode slurry, when the polymer content is 0.1%-2.0%, the slurry exhibits high maximum solids content, low filtration time, and high flexibility. When the polymer content is 0.2%-1.0% based on the total dry mass of the cathode slurry, both the electrode processing performance and the battery energy density can be further balanced.
[0477] Table 4
[0478]
[0479] As can be seen from the comparison between Example 7 and Example 20, the inclusion of a vinylidene fluoride polymer with a weight-average molecular weight of not less than 700,000 as a binder in the positive electrode slurry can further reduce the amount of binder used and improve the flexibility of the electrode sheet.
[0480] Table 5
[0481]
[0482] As can be seen from the comparison between Example 7 and Example 18, phosphate ester polymers can more effectively increase the solid content of the slurry, shorten the filtration time, and improve the flexibility of the electrode compared with phosphite polymers; moreover, phosphate ester polymers have better stability and can effectively improve the cycle capacity retention rate of the battery while improving the slurry dispersibility.
[0483] Table 6
[0484]
[0485] As can be seen from the comparison between Examples 26-28 and Comparative Examples 3-5, the polymer provided in the embodiments of this application can more effectively improve the dispersibility of positive electrode active materials with high carbon coating order, and simultaneously improve the processability, cycle stability and specific capacity of the battery by matching the dispersant with the coating layer on the surface of the positive electrode active material.
[0486] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A polymer, characterized in that, The polymer comprises the structure shown in Formula I. Formula I Wherein X includes a phosphate ester group or a phosphite ester group; R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment; R2 contains an organic segment, and the organic segment of R2 contains at least one of an amide group and an amino group, and the organic segment of R2 also includes C. 2-12 hydrocarbon group; The weight-average molecular weight of the polymer is 1000-10000.
2. The polymer according to claim 1, characterized in that, R2 includes the structure shown in Formula II. Formula II Among them, R4 and R5 are random copolymers, and R4 includes C 2-12 Hydroxyl group, C 3-13 At least one of the amide groups, R5 includes , , , At least one of them; Where q1, q2, q3, and q4 each independently include any integer between 0 and 4, and R6 a R6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
3. The polymer according to claim 1, characterized in that, R2 includes the structure shown in Formula III. Formula III Among them, R6 includes C 2-12 R7 includes alkylene groups. , At least one of the following; wherein q5 and q6 each independently include any integer between 0 and 4, and 1 ≤ n ≤ 6.
4. The polymer according to claim 1, characterized in that, The terminal group of R2 includes at least one of -C(O)-NH2 and -CH2-NH2.
5. The polymer according to claim 1, characterized in that, Both R1 and R3 contain polyether segments.
6. The polymer according to claim 1, characterized in that, At least one of R1 and R3 contains the polyether segment shown in Formula IV. Formula IV Where EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50.
7. The polymer according to claim 1, characterized in that, The end groups of the polyether segments include aryl groups.
8. The polymer according to claim 1, characterized in that, X includes phosphate ester groups.
9. The polymer according to any one of claims 1-8, characterized in that, The polymer includes at least one of the polymers shown in the following formula: 、 、 、 、 、 、 、 、 、 、 、 Among them, at least one of R1 and R3 contains the block copolymer polyether segment shown in Formula IV. Formula IV Where EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50, and R6 and R4 each independently include C 4-8 Alkylene, C 4-8 At least one of the subalkenyl groups.
10. The polymer according to claim 9, characterized in that, The end groups of the polyether segments include aryl groups.
11. The polymer according to claim 1, characterized in that, The polymer is shown in the following formula: R2 also includes at least one of hydrogen and aryl groups. At least one of R1 and R3 contains the block copolymer polyether segment shown in Formula IV. Formula IV Wherein EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50, and the end groups of the polyether segments include phenyl groups.
12. The polymer according to claim 1, characterized in that, The weight-average molecular weight of the polymer is 2000-5000.
13. A method for preparing a polymer, characterized in that, The preparation method includes: A polymer comprising the structure shown in Formula I is prepared by reacting the compound shown in Formula VI with R3OH, R1OH, water, and a polymeric monomer containing an unsaturated bond, wherein the polymeric monomer containing an unsaturated bond comprises at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond. Formula VI Formula I Wherein, X includes a phosphate ester group or a phosphite ester group, and X1, X2, and X3 all contain halogens; R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment; R2 includes an organic segment, and the organic segment of R2 contains at least one of an amide group and an amino group, and the organic segment of R2 also includes C 2-12 hydrocarbon group; The weight-average molecular weight of the polymer is 1000-10000.
14. The preparation method according to claim 13, characterized in that, The preparation method includes the following steps: The intermediate product shown in Formula VII is prepared by reacting the compound shown in Formula VI with R3OH, R1OH, and water in a first reaction. Equation VII The polymer is prepared by reacting the intermediate with a polymeric monomer containing at least one of an amide or an amine containing an unsaturated bond in a second reaction.
15. The preparation method according to claim 14, characterized in that, The second reaction specifically includes the following steps: The intermediate product undergoes an addition reaction with at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, followed by a substitution reaction with a halogen-substituted organic alcohol. The polymer was prepared by repeating the above addition and substitution reactions in sequence multiple times. R2 includes the structure shown in Equation III. Formula III Among them, R6 includes C 2-12 Hydrocarbon groups, R7 includes , At least one of the following; wherein q5 and q6 each independently include any integer between 0 and 4, and 1 ≤ n ≤ 6.
16. The preparation method according to claim 14, characterized in that, The preparation method further includes the following steps: The intermediate product is reacted with at least one of (i) an amide containing an unsaturated bond, an amine containing an unsaturated bond, or (ii) a hydrocarbon monomer containing an unsaturated bond, or a cyclic amide monomer in a third reaction to prepare the polymer, wherein R2 comprises the structure shown in Formula II: Formula II Among them, R4 and R5 are random copolymers, and R4 includes C 2-12 hydrocarbon group, C 3-13 At least one of the amide groups, R5 includes , , , At least one of them; Where q1, q2, q3, and q4 each independently include any integer between 0 and 4, and R6 a R6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
17. A method for preparing a polymer, characterized in that, The preparation method includes: The compound of formula VI is reacted with a starting material containing R3OH and R1OH to prepare a polymer containing the structure of formula I. Formula VI Formula I Wherein, X includes a phosphate ester group or a phosphite ester group, and X1, X2, and X3 all contain halogens; R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment, the end group of which includes an aryl group; R2 includes an organic segment, the organic segment of R2 contains at least one of an amide group and an amino group, and the organic segment of R2 also includes C 2-12 hydrocarbon group; The weight-average molecular weight of the polymer is 1000-10000.
18. Use of the polymer according to any one of claims 1 to 12 or the polymer prepared by any one of claims 13 to 17 as a dispersant.
19. A positive electrode slurry, characterized in that, Includes a dispersant, said dispersant comprising the polymer of any one of claims 1 to 12 or the polymer prepared by the preparation method of any one of claims 13 to 17.
20. The positive electrode slurry according to claim 19, characterized in that, The positive electrode slurry includes a positive electrode active material, which includes at least one lithium phosphate and its carbon-modified material.
21. The positive electrode slurry according to claim 20, characterized in that, The positive electrode active material includes at least one of lithium iron phosphate and its doped materials, lithium manganese iron phosphate and its doped materials, lithium iron phosphate and its doped materials with carbon coating, and lithium manganese iron phosphate and its doped materials with carbon coating.
22. The positive electrode slurry according to claim 20, characterized in that, The positive electrode active material includes a core and a carbon coating layer, wherein the carbon coating layer at least covers a portion of the surface of the core, and wherein the carbon coating layer contains sp 2 Hybridized carbon atoms and sp 3 The molar ratio of hybrid carbon atoms is not less than 0.
2.
23. The positive electrode slurry according to claim 22, characterized in that, sp in carbon coating layer 2 Hybridized carbon atoms and sp 3 The molar ratio of hybrid carbon atoms is not less than 0.
5.
24. The positive electrode slurry according to claim 22, characterized in that, sp in carbon coating layer 2 Hybridized carbon atoms and sp 3 The molar ratio of hybrid carbon atoms is not less than 0.
8.
25. The positive electrode slurry according to claim 22, characterized in that, The thickness of the carbon coating layer is no greater than 15 nm.
26. The positive electrode slurry according to claim 22, characterized in that, The thickness of the carbon coating layer is no greater than 10 nm.
27. The positive electrode slurry according to claim 22, characterized in that, The thickness of the carbon coating layer is 4nm-8nm.
28. The positive electrode slurry according to claim 19, characterized in that, Based on the total dry mass of the cathode slurry, the polymer content is 0.1%-2.0%.
29. The positive electrode slurry according to claim 19, characterized in that, Based on the total dry mass of the cathode slurry, the polymer content is 0.2%-1.0%.
30. The positive electrode slurry according to claim 19, characterized in that, The positive electrode slurry includes a binder, which includes a vinylidene fluoride polymer with a weight-average molecular weight of not less than 300,000.
31. The positive electrode slurry according to claim 30, characterized in that, The weight-average molecular weight of the adhesive is 700,000 to 9,000,000.
32. The positive electrode slurry according to claim 19, characterized in that, The maximum solid content of the positive electrode slurry shall not be less than 60%.
33. The positive electrode slurry according to claim 19, characterized in that, The maximum solid content of the positive electrode slurry is 60%-80%.
34. A positive electrode plate, characterized in that, The positive electrode sheet includes a positive electrode film layer, which is prepared by the positive electrode slurry according to any one of claims 19 to 33, or the positive electrode film layer includes a dispersant, which includes a polymer according to any one of claims 1 to 12 or a polymer prepared by the preparation method according to any one of claims 13 to 17.
35. The positive electrode sheet according to claim 34, characterized in that, The positive electrode sheet has a compaction density of 2.6 g / cm³. 3 The number of times it can be folded in half is no less than 2.
36. The positive electrode sheet according to claim 34, characterized in that, The positive electrode sheet has a compaction density of 2.6 g / cm³. 3 The number of times it can be folded in half is 3-6.
37. The positive electrode sheet according to claim 34, characterized in that, The areal density of the positive electrode sheet is not less than 300 mg / 1540.25 cm³. 2 .
38. The positive electrode sheet according to claim 34, characterized in that, The areal density of the positive electrode sheet is 300 mg / 1540.25 cm³. 2 -600 mg / 1540.25cm 2 .
39. The positive electrode sheet according to claim 34, characterized in that, The positive electrode film layer includes a dispersant, which comprises the structure shown in Formula I. Formula I Wherein X includes a phosphate ester group or a phosphite ester group, R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment or a polyester segment, R2 contains an organic segment, and the organic segment of R2 contains at least one of an amide group and an amino group, and the organic segment of R2 also includes C 2-12 hydrocarbon group; The positive electrode active material includes at least one of lithium iron phosphate and its doped materials, lithium manganese iron phosphate and its doped materials, lithium iron phosphate and its doped materials with carbon coating, and lithium manganese iron phosphate and its doped materials with carbon coating. Based on the total mass of the positive electrode film, the mass content of the dispersant is 0.1%-2.0%.
40. The positive electrode sheet according to claim 39, characterized in that, The end groups of the polyether segments include aryl groups.
41. The positive electrode sheet according to claim 39, characterized in that, The positive electrode active material includes at least one of lithium manganese iron phosphate and its doped materials, and lithium manganese iron phosphate and its doped materials with carbon coating.
42. The positive electrode sheet according to claim 39, characterized in that, The mass content of the dispersant is 0.2%-1.0%.
43. A secondary battery, characterized in that, The positive electrode sheet includes any one of claims 34 to 42.
44. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 43.
Citation Information
Patent Citations
Flame-retardant plasticizer and flame-retardant polymer-based composite material
CN113372550A
Polyoxyalkylene phosphonates and improved process for their synthesis
US20050227877A1
Ester polymer phosphate derivative and dispersant
WO2015020068A1